2011
DOI: 10.1029/2011gl047875
|View full text |Cite
|
Sign up to set email alerts
|

Passive monitoring of anisotropy change associated with the Parkfield 2004 earthquake

Abstract: [1] We investigate temporal variations in the polarization of surface waves determined using ambient seismic noise cross-correlations between station pairs at the time of the Mw 6.0 Parkfield earthquake of September 28, 2004. We use data recorded by the High Resolution Seismic Network's 3-component seismometers located along the San Andreas Fault. Our results show strong variations in azimuthal surface wave polarizations, Y, for the paths containing station VARB, one of the closest stations to the San Andreas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 22 publications
1
53
0
Order By: Relevance
“…By analyzing auto‐correlation functions in the source area, Ohmi et al [2008]found seismic velocity changes caused by the 2007 Noto Hanto Earthquake. Using ambient seismic noise cross‐correlations of the Parkfield event, Brenguier et al [2008a] observed a coseismic velocity decrease of 0.08% and a postseismic recovery process and Durand et al [2010] found an anisotropy change caused by the same earthquake. Chen et al [2010]analyzed wave velocity variations associated with the 2008 Wenchuan Earthquake by ambient noise cross‐correlations.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing auto‐correlation functions in the source area, Ohmi et al [2008]found seismic velocity changes caused by the 2007 Noto Hanto Earthquake. Using ambient seismic noise cross‐correlations of the Parkfield event, Brenguier et al [2008a] observed a coseismic velocity decrease of 0.08% and a postseismic recovery process and Durand et al [2010] found an anisotropy change caused by the same earthquake. Chen et al [2010]analyzed wave velocity variations associated with the 2008 Wenchuan Earthquake by ambient noise cross‐correlations.…”
Section: Introductionmentioning
confidence: 99%
“…[, ]; Brenguier et al . [])), variations in crustal scattering [ Audet , ], and variations in the polarization of surface waves [ Durand et al ., ], as well as studies of GPS and InSAR data (e.g., Johanson et al . []; Johnson et al ., ; Freed , []).…”
Section: Introductionmentioning
confidence: 99%
“…Even so, several authors have presented the full matrix of possible time‐domain ambient noise correlations from three‐component instruments (Campillo & Paul 2003; Stehly et al. 2007; Roux 2009; Durand et al. 2011; Roux et al.…”
Section: Introductionmentioning
confidence: 99%